Exploring ideological-political education in English classrooms: A survey of compulsory education schools in Dazhou, China - Liu, Yanshi (Educational Challenges, 2025)
Purpose. This article endeavors to gain insights into the current state of curriculum ideological-political education integration within English classroom teaching in China’s compulsory education system, using two schools in Dazhou as case studies. It aims to dissect prevalent issues and their underlying causes, ultimately exploring and proposing effective strategies for enhancing this integration. Methodology. Utilizing a concurrent mixed-methods approach, this study incorporates both quantitative and qualitative analyses. Specifically, it employs surveys and interviews to investigate and assess the practical incorporation of ideological-political education elements into English classes in compulsory education. Results. The findings indicate that English teachers in Dazhou’s compulsory education sector possess a commendable comprehension of curriculum ideological-political education. However, they show insufficient attention to ideological-political elements in their actual teaching practices. Relying predominantly on traditional lecturing methods, the implementation of ideological-political education appears sermonizing, resulting in suboptimal outcomes. Teachers also exhibit knowledge deficiencies in areas such as implicit curriculum and the fundamental tasks of moral education, necessitating enhancements in these domains. Conclusions. The study underscores the need for teachers to deepen their understanding of curriculum ideological-political education and improve their integration skills. Relevant schools should prioritize moral education, leveraging ideological-political education to foster students’ holistic development. Strengthening teacher training and evaluation systems is also pivotal in addressing these gaps and enhancing the overall effectiveness of ideological-political education integration in English classrooms.